Improving Students' Communication Skills Through the Problem Posing Method in MTs Al-Ishlahiyah Binjai Students - Fitria, Cindy; Pohan, Indra Satia; Hemawati, Hemawati (Lembaga Riset Mutiara Akbar, 2024)
Communication skills are very important in conveying messages or ideas. Students at MTs. Al Ishlahiyah are seen to be less able to convey ideas or ideas, especially in class learning forums. Therefore, the teacher needs to make efforts in improving students' communication skills. Therefore, the teacher mostly uses the problem posing method in learning. Therefore, this research aims to find out how the application of the problem posing method by teachers in improving student communication at MTs Al Ishlahiyah Binjai. This research method was conducted using a field approach and using descriptive qualitative research. The data source used is information obtained from data sources, namely teachers and students at MTs Al Ishlahiyaj Binjai. From the results of the research and the statement above, we can describe and explain that we can conclude and adjust that improving communication skills through the problem posing method is very helpful for students in improving students' communication skills in giving questions, statements, information, and also ideas or ideas in the learning process and also students look more active in compiling statements according to the situation they are facing at that time and students are also more visible to be able to solve their own problems without the help of others and also students will be more able to master the material.